INFOGRAFIS PENCEGAHAN COVID 19 MELALUI EKSPLORASI DOKUMENTASI VIDEO PROJECTION MAPPING - Nur Rahmat Ardi Candra Dwi Atmaja; Johan Ies Wahyudi; Damar Tri Afrianto (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2021)
The process of changing the initial shape of a facade into a new shape resulting in an optical illusion is an activity called Video Mapping. These objects will visually change from their usual form into a new form that is different and very fantastic. Projection mapping is a medium that can provide the audience with experience to feel three-dimensional effects in two-dimensional fields, or it can also be called immersive media. With the display of a projection mapping on a flat plane, it is possible to reach a wider segment of the material and content regarding government policies related to the Covid-19 preventive health protocol which can be displayed through projection video mapping media. Planning to create work for the Video Projection Mapping Documentation is none other than the departure from anxiety about the presence of conventional media and social media which report simply and monotonously related to government policies related to the prevention of Covid-19 and its health protocols. This is what causes people to just casually respond to the infographic because the content and visualization lack persuasive, dramatic and creative power. Because of this, a method of art creation is formulated in this artistic research, namely how to create infographics that emphasize new media as an alternative media for socializing government policies related to Covid-19 through the creation of the work Documentation Video Projection Mapping as an alternative media for the socialization of Covid-19 prevention. Keywords: infografis, ekplorasi, video dokumentasi, projection mapping